Comparison of microwave assisted extraction with hot reflux extraction in acquirement and degradation of anthocyanin from powdered blueberry - Yu, Sun; Hongkun, Xue; Chenghai, Liu; Chai, Liu; Xiaolin, Su; Xianzhe, Zheng (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Acquirement and degradation kinetics of anthocyanin from powdered blueberry were studied to analyze the degradation reason and improve the yield of anthocyanin under microwave assisted extraction (MAE) conditions. Hot reflux extraction (HRE) method was employed as a reference with MAE to discriminate the influences of the microwave irradiation under the same extraction temperature at 30°C-70°C. Ethanol was selected as extraction solvent. Microwave volumetric heating improves the diffusion and solubility of anthocyanin within powdered blueberry particles in the pre-heating period. The kinetic coefficients, in terms of delivery kinetic and diffusion kinetic, are lower in MAE than that in HRE. Four anthocyanins including delphinidin, cyanidin, malvidin and pelaronidin were detected in the anthocyanin extracts from blueberry. Delphinidin, cyaniding, and pelargonidin contents significantly decrease, but malvidin was unchanged in MAE. Anthocyanin yield increases with elevating extraction temperatures, but anthocyanin degradation occurred at 41.2°C. The acquirement amount of anthocyanin is lower than its degradation amount when microwave extraction temperature is higher than 53.6°C. The self-aggregation of anthocyanin molecules and degradation results in the reduction of anthocyanin yield extracted from blueberry powder. In MAE, microwave volumetric heating results in the rapidly elevated temperature in pre-heating stage and generation of internal pressure to improve the acquirement of anthocyanin and the non-thermal effect from microwave field may weak the effect of temperature to decline the degradation of anthocyanin to monomer. The non-thermal microwave irradiation has pronounced effects compared to the effects of temperature on the structure changes of anthocyanin molecules at extraction temperature below 50°C. In HRE, convection mode of heat transfer in extraction system form the non-uniform distribution of temperature in the extraction vials to decrease the acquirement yield of anthocyanin from the blueberry powder. The research results provide valuable data to optimize extraction temperature for high extraction yield and bioactivity of anthocyanin in microwave extraction process. Keywords: blueberry, microwave, anthocyanin, degradation, extraction, temperature, kinetic DOI: 10.3965/j.ijabe.20160906.2724 Citation: Sun Y, Xue H K, Liu C H, Liu C, Su X L, Zheng X Z. Comparison of microwave assisted extraction with hot reflux extraction in acquirement and degradation of anthocyanin from powdered blueberry. Int J Agric & Biol Eng, 2016; 9(6): 186－199.